2005
DOI: 10.1111/j.1475-1313.2005.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strabismus on a young child's selection of a playmate

Abstract: As only 11% of the children consistently selected against playmates with strabismus, and about the same percentage preferred playmates with strabismus (12%), the presence of strabismus does not appear to be a significant factor in peer acceptance in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…This finding has been previously documented (Koch, 1957; Alexander and Hines, 1994; Hoffmann and Powlishta, 2001). A study designed similarly to the current study found that children’s choice of playmates was not affected by an eye turn (Johns et al. , 2005), and another study of first‐grade children also found that spectacles do not play a role in choosing their friends (Terry and Stockton, 1993).…”
Section: Discussionsupporting
confidence: 57%
“…This finding has been previously documented (Koch, 1957; Alexander and Hines, 1994; Hoffmann and Powlishta, 2001). A study designed similarly to the current study found that children’s choice of playmates was not affected by an eye turn (Johns et al. , 2005), and another study of first‐grade children also found that spectacles do not play a role in choosing their friends (Terry and Stockton, 1993).…”
Section: Discussionsupporting
confidence: 57%
“…(Paysse et al, 2001, Uretman et al, 2003) Nevertheless, some previous studies have shown a surprising lack of teasing and bullying in children with strabismus. (Horwood et al, 2005, Johns et al, 2005, Sabri et al, 2006) It is also possible that since children with intermittent XT are mostly able to control the exodeviation at conversational distances, the exodeviation largely goes unnoticed by peers.…”
Section: Discussionmentioning
confidence: 99%
“…Amblyopia, loss of vision, and cosmetic stigma are some of the consequences of untreated strabismus [7]. Some studies showed that strabismus is one of the common eye conditions having a potential subsequent impact on the psychological and socioeconomic domains later in the life of individuals suffering from strabismus [8][9][10], as well as on the effects on their selfimage and interpersonal relationships with others, and plays a major role in selecting a partner for adults and in selecting a playmate for children [11][12][13].…”
Section: Introductionmentioning
confidence: 99%